Effects of experimental volleyball rules quantified by type and number of jumps, hits and contacts - Stankovic, M.; Peric, D.; Ruiz-Llamas, G.; Quiroga-Escudero, M. E. (SportMont, 2017)
The purpose of this study was to determine the influence of the two new rules tested at the inaugural U23 Men`s Volleyball World Championship (21-point set excluding the fifth set, and 15 seconds between rallies-10 seconds from the finished point until the referee`s whistle for serve and five seconds for performing the serve) on number and types of jumps and number of contacts and hits. The analysis comprised 25,930 jumps (an essential physical activity for volleyball), 15,706 contacts and 10,224 hits during 36 matches played by 144 males aged under 23 at the first Under 23 Men`s World Championships organized in Uberlandia, Brazil, in 2013. Two investigations were conducted: 1) Analysis of jumps by Jump type, In-game role and Level of set win; 2) Analysis of contacts (reception, setting, block, defense) and hits (serve and attack) by Type, In-game role and Set outcome. Significant differences (p=0.000) were found between in-game role and jump type, as Middle blocker performed the most (34.7%), followed by Outside hitter (24.9%), Setter (24.6%) and Opposite (15.8%). Significant differences were found for number and types of Hits between set Winner and Loser teams only for serves by Setter (p